2017
DOI: 10.3390/s17112612
|View full text |Cite
|
Sign up to set email alerts
|

Gas Measurement Using Static Fourier Transform Infrared Spectrometers

Abstract: Online monitoring of gases in industrial processes is an ambitious task due to adverse conditions such as mechanical vibrations and temperature fluctuations. Whereas conventional Fourier transform infrared (FTIR) spectrometers use rather complex optical and mechanical designs to ensure stable operation, static FTIR spectrometers do not require moving parts and thus offer inherent stability at comparatively low costs. Therefore, we present a novel, compact gas measurement system using a static single-mirror Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 23 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Additionally, with the use of a gas cell that allows an optical pathlength of up to 120 Hz, gases in the low ppm range can be accurately quantified. 196 The experimental protocol for quantitative IR measurements of gas sorption by solid materials is described in detail by Drenchev et al 16 The procedure and the power of the technique is demonstrated by the water-enhanced CO 2 adsorption on a metal-organic framework, UiO-66. For this purpose, a custommade system, consisting of a combination of high-and lowtemperature sample cells, was designed.…”
Section: Gas Sorption and Desorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, with the use of a gas cell that allows an optical pathlength of up to 120 Hz, gases in the low ppm range can be accurately quantified. 196 The experimental protocol for quantitative IR measurements of gas sorption by solid materials is described in detail by Drenchev et al 16 The procedure and the power of the technique is demonstrated by the water-enhanced CO 2 adsorption on a metal-organic framework, UiO-66. For this purpose, a custommade system, consisting of a combination of high-and lowtemperature sample cells, was designed.…”
Section: Gas Sorption and Desorptionmentioning
confidence: 99%
“…Additionally, with the use of a gas cell that allows an optical pathlength of up to 120 Hz, gases in the low ppm range can be accurately quantified. 196…”
Section: Gas Sorption and Desorptionmentioning
confidence: 99%
“…In 2018, Yan et al proposed a highresolution channel imaging spectral polarimeter using a liquid crystal variable retarder (LCVR) [13,14], the simulation experiment results showed that in the working range of 0.48-0.96 μm, the theoretical resolution of the spectrum could reach 40 cm −1 . In 2019, Michael et al proposed a mid-wave infrared hyperspectral imager based on a single-mirror interferometer structure [15][16][17][18], the hyperspectral data cube was obtained by the windowing method, and a spectral resolution of 12 cm −1 was achieved in 3.8-13 μm.…”
Section: Introductionmentioning
confidence: 99%
“…Temporally and spatially modulated Fourier transform imaging spectrometers (TSMFTIS) are a type of hyperspectral imaging sensors developed for airborne/spaceborne hyperspectral imaging. 16 A focal plane array (FPA) is usually used as the two-dimensional (2D) detecting sensor in TSMFTISs. However, because of the defects of the materials, the temperature unevenness of the production unit, the etching chemical material impure, manufacturing process, or other factors, certain pixels in the detector behave abnormally and are therefore called bad pixels, defect pixels, or blind pixels.…”
Section: Introductionmentioning
confidence: 99%